Analysis Of Using Islamic Bank Social Media And Website In The E-Marketing Concept Using Attention, Interest, Search, Action, Share (AISAS) Methods - Silmi Safira; Iqbal Fadli Muhammad; Muhammad Doddy (Jurnal Ekonomi dan Perbankan Syariah, 2019)
This study aims to analyze the extent to which Islamic banks, especially sharia commercial banks, have used websites and social media in the concept of e-marketing. The scope of this research is 13 Islamic commercial banks. The method used is the AISAS method (Attention, Interest, Seacrh, Action, Share). The result is that from the 13 Islamic banks, the top 5 banks in utilizing websites and social media for e-marketing are: Bank Syariah Mandiri, Bank BNI Syariah, Bank Muamalat, BRI Syariah Bank, and BJB Syariah Bank. implication of this study is that Islamic banking is better at maximizing the approach to the community by utilizing digital media to get the attention of customers or prospective customers. Because in modern times social media is something that is so important for people's lives.